Feminist Pedagogy: A Political Position - Rocky Gerung (Yayasan Jurnal Perempuan, 2016)
Feminist pedagogy is a mode of thought, and a policy reform proposal. It leads the academic discourse analysis to find out the political location of injustice in the history of knowledge and in the nexus of power. Social transformation is the ultimate goal of feminist pedagogy.